The emerging role of RNA modifications in the regulation of mRNA stability - Boo, Sung Ho; Kim, Yoon Ki (Experimental & molecular medicine, 2020)
Many studies have highlighted the importance of the tight regulation of mRNA stability in the control of gene expression. mRNA stability largely depends on the mRNA nucleotide sequence, which affects the secondary and tertiary structures of the mRNAs, and the accessibility of various RNA-binding proteins to the mRNAs. Recent advances in high-throughput RNA-sequencing techniques have resulted in the elucidation of the important roles played by mRNA modifications and mRNA nucleotide sequences in regulating mRNA stability. To date, hundreds of different RNA modifications have been characterized. Among them, several RNA modifications, including N 6 -methyladenosine (m 6 A), N 6 ,2′- O -dimethyladenosine (m 6 Am), 8-oxo-7,8-dihydroguanosine (8-oxoG), pseudouridine (Ψ), 5-methylcytidine (m 5 C), and N 4 -acetylcytidine (ac 4 C), have been shown to regulate mRNA stability, consequently affecting diverse cellular and biological processes. In this review, we discuss our current understanding of the molecular mechanisms underlying the regulation of mammalian mRNA stability by various RNA modifications. Gene activity: the significance of RNA modification Messenger RNA molecules play their key role in directing the manufacture of proteins via translating the genetic information in DNA. Sung Ho Boo and Yoon Ki Kim at Korea University in Seoul review current understanding of the significance of modifications to messenger RNA with respect to RNA stability in mammalian cells. Recent advances in RNA sequencing technology have revealed hundreds of different modifications which, by influencing RNA stability, can control gene expression. The modifications largely involve small chemical groups added to any of the four nucleotide groups that make up an RNA molecule. This can affect all aspects of mature RNA biogenesis, including transcription, pre-mRNA splicing, RNA export form the nucleus to the cytoplasm, translation, and stability.